Design and application of a sterile urine culture specimen retention device with negative pressure suction device (一种带负压吸引装置的无菌尿培养标本留取装置的设计与应用) - QIAN Xiaoge (茜晓格); SUN Xiumei (孙秀梅) (中西医结合护理)
This study introduces a sterile urine culture specimen retention device with negative pressure suction device. By setting puncture needles, guide tubes, negative pressure structures, and collectors, the rapid retention of sterile urine culture specimens can be achieved. The entire process of urine is always in a sterile environment, which not only ensures the retention of sterile culture specimens to the greatest extent possible, improves the authenticity of specimen results, but also is easy to operate and mastered by nurses, It can reduce the occurrence of needle injuries, effectively protect medical personnel, reduce the exposure risk of contacts, reduce the workload of nursing staff, and improve nursing work efficiency. (本研究介绍一种带负压吸引装置的无菌尿培养标本留取装置, 通过设置穿刺针、导流管、负压结构和收集器能够实现无菌尿培养标本的快速留取, 不仅可以有效保证无菌状态, 提高标本结果的真实性, 而且操作简单, 护士较容易掌握, 能够降低发生针刺伤的风险, 提高护理工作效率 。)